Simultaneous detection of three pome fruit tree viruses by one-step multiplex quantitative RT-PCR - Malandraki, Ioanna; Beris, Despoina; Isaioglou, Ioannis; Olmos, Antonio; Varveri, Christina; Vassilakos, Nikon (2018)
A one-step multiplex real-time reverse transcription polymerase chain reaction (RT-qPCR) based on TaqMan probes was developed for the simultaneous detection of Apple mosaic virus (ApMV), Apple stem pitting virus (ASPV) and Apple stem grooving virus (ASGV) in total RNA of pome trees extracted with a CTAB method. The sensitivity of the method was established using in vitro synthesized viral transcripts serially diluted in RNA from healthy, virus-tested (negative) pome trees. The three viruses were simultaneously detected up to a 10(-4) dilution of total RNA from a naturally triple-infected apple tree prepared in total RNA of healthy apple tissue. The newly developed RT-qPCR assay was at least one hundred times more sensitive than conventional single RT-PCRs. The assay was validated with 36 field samples for which nine triple and 11 double infections were detected. All viruses were detected simultaneously in composite samples at least up to the ratio of 1: 150 triple-infected to healthy pear tissue, suggesting the assay has the capacity to examine rapidly a large number of samples in pome tree certification programs and surveys for virus presence.